EKSEKUSI PEMBAYARAN UANG PENGGANTI DALAM PERKARA TINDAK PIDANA KORUPSI - , MUHAMMAD ARAS MADUSIRA, S.H ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this research is to find out executions in the decision of payment of compensation that can not be paid entirely by the prosecutor convicted of corruption and efforts for the payment of money to be paid entirely the compensation in corruption cases. This research is a normative-empirical research, ie research that is done by researching library materials and field data as the main supporter. Based on the result, executions in the decision of payment of compensation, can not be fully paid by the convicted of corruption, because: First, the Act Corruption is not set if the convicted person pays only a partial payment of compensation. Second, the prosecution has not used the maximum eksekutorialnya function in collecting payment of compensation. Third, convicted of corruption would prefer serving a jail subsidiary / legal entity rather than pay compensation. Fourth, the confiscation of property made after the case convicted of corruption the remain legal force. Fifth, or the last, do not use a civil lawsuit to the settlement payment of compensation. Conclusions in this research, for execution of criminal in the decision of payment of compensation to be paid entirely by the convict, the prosecutor must do: First, to maximize the discretion to substitute cash payments. Second, to maximize the efforts of non-litigation by prisoners or their families through alternative dispute resolution including: negotiation, mediation, conciliation and arbitration. Third, improve the quality of the State Attorney Lawyers. Fourth, or the last, to confiscate any early and maximize community participation in discovering the wealth convicted of corruption